Considerations in dental treatment of pediatric patients with hemophilia: A case report. - Lorena Bravo; Daniela Muñoz (Universidad de Concepción., 2012)
A male patient, 7 years old, attends the Regional Hospital of Guillermo Grant Benavente derived by a presumptive diagnosis of hemophilia due to bleeding resulting from extraction of a primary tooth and a family history. A hematologic study was realized, where was observed that the factor VIII was decreased, which confirmed the diagnosis. For dental treatment was coordinated with the treating hematologist for inpatient management and control of hematologic parameters during invasive dental procedures, by the administration of factor VIII.